1977
DOI: 10.1002/1097-0142(197708)40:2<846::aid-cncr2820400238>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Hyperparathyroidism in persons treated with x-rays for tuberculous cervical adenitis

Abstract: Follow-up examinations of one hundred persons treated with x-rays for tuberculous adenitis between 1930 and 1946 have been carried out to determine if there is an increased incidence of hyperparathyroidism (HPT) after radiation exposure. Neck explorations were done in patients with hypercalcemia and signs and symptoms compatible with HPT. Individuals with thyroid masses were also operated upon when examination of fine needle specimens gave suspicions of malignancy. Eleven subjects were found to have developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

1978
1978
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(20 citation statements)
references
References 16 publications
2
17
1
Order By: Relevance
“…The radiation dose of our patients also appears similar to that of other investigators' patients [ 11,131, a]-though Tisell et a1 [12] suggested that primary hyperparathyroidism was more frequent among patients who had been heavily exposed to radiation. The radiation dose of our patients also appears similar to that of other investigators' patients [ 11,131, a]-though Tisell et a1 [12] suggested that primary hyperparathyroidism was more frequent among patients who had been heavily exposed to radiation.…”
Section: Discussionsupporting
confidence: 86%
“…The radiation dose of our patients also appears similar to that of other investigators' patients [ 11,131, a]-though Tisell et a1 [12] suggested that primary hyperparathyroidism was more frequent among patients who had been heavily exposed to radiation. The radiation dose of our patients also appears similar to that of other investigators' patients [ 11,131, a]-though Tisell et a1 [12] suggested that primary hyperparathyroidism was more frequent among patients who had been heavily exposed to radiation.…”
Section: Discussionsupporting
confidence: 86%
“…21,22 Recently, polymorphisms in the VDR gene were shown to predispose to pHPT, so far representing the only known genetic risk factor for the disease. 20 Parathyroid adenomas are mainly monoclonal tumors, 23 which arise from a single precursor cell with an acquired growth advantage compared with the surrounding tissue.…”
Section: Discussionmentioning
confidence: 99%
“…A history of radiation therapy of the neck was noted in the hospital records of six patients. Such therapy is a well known risk factor for both thyroid cancer (34)(35)(36)(37) and hyperparathyroidism (38)(39)(40)(41)(42)(43). Since in all cases, several years elapsed between radiation therapy and manifestations of the neck tumor, it is possible that more patients with a combination of parathyroid adenoma and thyroid carcinoma may have had such therapy over the neck as children.…”
Section: Relative Risk By Observation Timementioning
confidence: 99%